(untitled) (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background: Based on Statistics Indonesia in 2014 for HIV/AIDS cases showed an increase in the reported number of HIV/AIDS from January 1 to September 30, 2014 amounted to 22 869 people living with HIV and 1.876 for people with AIDS. The cumulative number is highest at age 20-29 years and 9796 patients already have death. Yogyakarta Special Region has now ranks 14th as a province that has people living with HIV/AIDS in Indonesia’s largest. Total cumulative from 1 April 1987 to 30 September 2014 as many as 2,611 in phase HIV dan 916 has entered the phase of AIDS Objective: To determine the effect of education on HIV/AIDS to increase knowledge about HIV/AIDS in class XI student of SMAN 1 Kretek, Bantul, Yogyakarta. Methods: This research method is Pre-Experimental. The design of this study is one group pre-test post-test. The sampling technique using proportional random sampling. Calculation of sample size was obtained by 46 respondents. The samples in this study was taken from each class with absent odd number, take 3 classes in a class of 12 people and one taken 10 people. Results: The results of pre-test counseling about the effects of HIV/AIDS to increase knowledge of students of class XI SMA Negeri 1 Kretek, Bantul, Yogyakarta on HIV/AIDS, most students have less knowledge of 40 students (87%). Results of the post-test after counseling on HIV/AIDS to increase the knowledge class XI SMA Negeri 1 Kretek, Bantul, Yogyakarta, most respondents have enough knowledge to 34 students (73.9%). Conclusion: The effect of counseling on HIV/AIDS is very effective for increasing knowledge about HIV/AIDS in class XI student of SMAN 1 Kretek, Bantul, Yogyakarta. Evidenced by no significant difference before and after counseling on HIV/AIDS in class XI student of SMAN 1 Kretek, Bantul, Yogyakarta, ie 0.000 <0.05 significance value of 0.000 (p <0.05). Keywords: Education, Science, Youth